Answer:
2 1/6
Step-by-step explanation:
Because the denominators are different, and there are whole numbers involved, then first make the fractions improper.
4 1/2 -> 9/2
6 2/3 -> 20/3
Next, make the denominators the same by multiplying each fraction by the denominator of the other.
9/2 * 3 = 27/6
20/3 * 2 = 40/6
Then you can subtract the numerators because the denominators are the same:
40/6-27/6= 13/6
Then you can convert to a mixed fraction if need be.
The answer is going to be 5f + 2e <span> hopes this helps :)
</span>
Answer:
2.
A. (P+h)(x)
2x/x+4 (x-1) + x/x-1 (x+4)
2x^2-1/x^2-4
+
X^2+4/x^2-4
= 3x^2+3/x^2-4
B. (F-g)(x)
X^2-7x+6-x - 6
= x^2 -8x
C. (Fg)(x)
(X^2-7x+6)(x-6)
= x^3-13x^2+48x-36
D. (H/p)(x)
X/x-1 / 2x/x+4
X/x-1 / x+4/2x
= X^2+4x/2x^2-2x
3.
A. (F+g)(3)
X^2+1 + x-4
3^2+1 + 3-4
10 -1
= 9
B. (f-g)(0)
X^2+1 - x-4
0+1 -0-4
1-4
= -3
C. (Fg)(-k)
(X^2+1) (x-4)
(-k^2+1) (-k-4)
K^3+4k^2-k-4
D. (F/g)(k-2)
X^2+1 /x-4
K-2^2+1 / k-2 -2
= K^2-4k+5 / k-4
Step-by-step explanation:
Answer:
(x−4)2(x2+4x+16)
Step-by-step explanation:
here hope this helpsss
1. The second dot
2. The first dot :))